Challenges and success factors for small and medium enterprises in the food sector in the Riyadh region (International Journal of Financial, Administrative and Economic Sciences, 2024)
Small and medium-sized enterprises (SMEs) in the food sector in Riyadh face various challenges and factors affecting their success. This research aims to identify the main challenges encountered by SMEs in the food sector in Riyadh, explore the strategies they adopt, and analyze the success factors contributing to the growth and sustainability of these SMEs. The researchers employed a descriptive survey method, suitable for the nature and objectives of the study, and selected 52 SME owners from the study population. The study revealed several key findings: the overall average response of the study participants regarding the challenges and difficulties faced by SMEs fell at a "agree" level with an average score of 4.02. Additionally, the overall average response of the study participants regarding the success factors of SMEs fell at a "strongly agree" level with an overall average score of 4.51. Furthermore, the overall average response of the study participants regarding marketing and promotion in SMEs fell at a "agree and strongly agree" level with an overall average score of 4.40. The study recommended that educational and training programs specialized for SME owners in the food sector be provided, including marketing, cost management, and development of managerial skills, to increase their understanding and enhance their capabilities in dealing with financial and marketing challenges. Academic institutions should be encouraged to provide greater support for research and innovation in the food industry, including providing funding and necessary resources for researchers to focus on innovative solutions to the challenges facing SMEs in this sector. Universities and academic institutions should support SMEs in the food sector in updating their technology and applying modern technological solutions to improve their productivity, product quality, and more effective marketing.
Keywords: Success Factors; Small Enterprises; Medium Enterprises; Food Sector